2017
DOI: 10.1039/c6ra28263f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures and catalytic activity of cyclometalated rhenium complexes

Abstract: Several five-membered cyclometalated rhenium complexes (1–5) were synthesized, and their photocatalytic activity on direct arylation of arenes with aryl halides was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…At present, there is great interest in peri-substituted 8-diorganophosphinonaphth-1-yl and 6-diorganophosphinoacenaphth-5-yl precious metal compounds of Re, [1] Ru, [2,3] Ir, [4] Rh, [5] and particularly, Au, [6][7][8][9][10][11][12][13][14][15][16] which involves the synthesis, bonding analysis and applications in bond activation and catalysis. Often, the synthesis of these compounds entails the oxidative addition of the metal to a C-H [1][2][3][4][5] or C-X (X = halide) bond in peri-position to a structurally directing P atom that takes part in coordination to the precious metal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is great interest in peri-substituted 8-diorganophosphinonaphth-1-yl and 6-diorganophosphinoacenaphth-5-yl precious metal compounds of Re, [1] Ru, [2,3] Ir, [4] Rh, [5] and particularly, Au, [6][7][8][9][10][11][12][13][14][15][16] which involves the synthesis, bonding analysis and applications in bond activation and catalysis. Often, the synthesis of these compounds entails the oxidative addition of the metal to a C-H [1][2][3][4][5] or C-X (X = halide) bond in peri-position to a structurally directing P atom that takes part in coordination to the precious metal.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is great interest in peri-substituted 8-diorganophosphinonaphth-1-yl and 6-diorganophosphinoacenaphth-5-yl precious metal compounds of Re, [1] Ru, [2,3] Ir, [4] Rh, [5] and particularly, Au, [6][7][8][9][10][11][12][13][14][15][16] which involves the synthesis, bonding analysis and applications in bond activation and catalysis. Often, the synthesis of these compounds entails the oxidative addition of the metal to a C-H [1][2][3][4][5] or C-X (X = halide) bond in peri-position to a structurally directing P atom that takes part in coordination to the precious metal. [6][7][8][9][10][11][12][13][14] Recently, we have used the well-defined 5-diorganophosphinoacenaphth-6-yllithium, RLi (1, R = 5-Ph 2 P-Ace-6-), [17] as starting material for the synthesis of two related transmetallation reagents R 2 Hg (2, R = 6-Ph 2 P-Ace-5-) [15] and RSnBu 3 (3, R = 6-Ph 2 P-Ace-5-), [18] which offer the advantage to be nonreductive and bench stable (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Alkylation of electron rich arenes immediately draws attention to the possibility of a Friedel–Crafts type mechanism (electrophilic aromatic substitution) whereby a cationic intermediate derived from the alkene is trapped by the electron-rich arene (Scheme A). Alternatively, a Re-catalyzed C–H activation processes may be operational and such reactions have been previously reported. , The hydroxyl group could act as a directing group for metalation of the arene via a C–H activation-type mechanism, with an alkene hydrometalation process occurring either after or prior to the C–H activation step (Scheme B,C, respectively) and in either case followed by a reductive coupling step. The hydrometalation event could be a concerted 1,2-metal hydride insertion into the alkene or alternatively proceed via a 2-step process in which hydrogen atom transfer (HAT) to the olefin provides a radical pair that subsequently recombines to afford a net hydrometalation; a subsequent reductive coupling could afford product.…”
Section: Potential Reaction Mechanismsmentioning
confidence: 99%
“…Rhenium is a grayish colored metal, rare in nature, with many attractive properties that have proven useful in superalloys, the petrochemical industry, electrodes for fuel cells and advanced catalytic applications. [17][18][19][20][21][22][23] The increased availability of rhenium and greater knowledge of its chemistry have excited increasing research on its lubricating applications. Researchers have shown that some rhenium oxides possess a friction-reducing quality at high temperature.…”
Section: Introductionmentioning
confidence: 99%